Necrotizing Fasciitis due to Candida Infection after Thyroid Surgery - Mustafa Aslıer (Turkish Archives of Otorhinolaryngology, 2020)

(untitled)
Surgical site infections (SSIs) after thyroidectomy are very rare as it is a clean case surgery, even the patterns for the use of prophylactic antibiotics is disputable. Cutaneous and subcutaneous tissue infections are the most common type of SSIs that develop due to the contamination of the skin flora pathogens during surgical incision. We report the case of a patient who, unlike the reports in the literature, developed necrotizing fasciitis due to Candida infection after total thyroidectomy. A 65-year-old male patient developed SSI progressing to necrotizing fasciitis four days after total thyroidectomy. Rapidly progressive necrosis was observed until antifungal treatment was initiated. Tissue defect eventually recovered with complete epithelization 40 days after the operation.